Evolution of European Union’s policy towards the Mediterranean region - Diawol, Anna (Acta Agraria Debreceniensis, 2012)
This paper examines some specific problem in Euro Mediterranean relation. Author decided to concentrate on two main issues: the characteristics of the institutions of the Union for the Mediterranean, indicating similarities and differences in the Euro-Mediterranean programs and the presentation of specific new initiatives. The author will also summarize the main possible positions in the ongoing debates about the need to reform the European Union addressed to the countries of North Africa and the Middle East.